Do Science and Common Wisdom Collide or Coincide in their Understanding of Relational Aggression? - Doyle, Heather; Mcloughlin, Caven S. (Frontiers in Psychology, 2010)
Relational aggression is a form of covert or indirect aggression or bullying in which harm is caused through damage to relationships or social status within a group, rather than through physical violence. We compare findings from empirical research into relational aggression with the depictions, interpretations and interventions described in trade-books and popular media dealing with that same topic. Relational aggression is more common and more studied among girls than boys and is popularly described as synonymous with “mean-girl” behaviors. We investigate the degree that popular trade books and movies accurately portray findings from researched investigations including the incidence and indicators of the condition and its remedies. We determine that there is a great deal of similarity between these two sources in how relational aggression is understood and how it may be treated. The concurrence across both dissemination formats reflects terminology and definitions, the harmful effects of relational aggression, the gender-specific nature of the condition to women and girls, its age of occurrence, the impact of parenting styles, its relationship to girls’ social competence, and nature of its expression through non-physical means.